PENGARUH PENGOBATAN REFLUKS LARING FARING TERHADAP WAKTU TRANSPORTASI MUKOSILIAR HIDUNG - GESIT PURNMA GIANA DETA; VEBY NOVRI YENDRI; ALGITA ALGITA (JURNAL ILMIAH SIMANTEK, 2023)
It is necessary to identify changes in nasal mucociliary transport time (TMS) in laryngeal-pharyngeal reflux (RLF) patients before and after treatment.This study used the pre and post test method design using the saccharin test. The data obtained will be analyzed bivariately. Testing the RSI and RFS variables using the Wilcoxon test. Testing the TMS variable uses the Paired t-test. The results of the Wilcoxon test with a 95% confidence level, the Z value of the RSI was -4,002 and the RFS was -3,234 so that there were differences in the RSI and RFS variables before and after treatment. Paired t-test results with a 95% confidence level, the Z value obtained from TMS was 3,717 so that there were differences in the TMS variables before and after treatment. The results of this study showed that there were statistically significant differences in the timing of nasal TMS in RLF patients before and after treatment.